Evaluation of bread wheat genotypes under rain-fed conditions in Terai districts of Nepal - Pandey, Deepak; Pant, Khem Raj; Bastola, Biswas Raj; Giri, Rabin; Bohara, Suman; Shrestha, Shankar; Hamal, Govinda Bahadur; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2021)
Thirty four percent of the total wheat cultivated area is under rain-fed condition in Nepal and that of the Terai is nineteen percent. The objective of this study was to develop drought tolerant and high yielding varieties of wheat for timely sown rain-fed environments. Coordinated Varietal trial (CVT) was carried out in normal wheat growing season during 2016/17 and 2017/18. The research was conducted at five locations (Rampur, Bhairahawa, Doti, Jitpur and Nepalgunj) of five research stations of Nepal Agricultural Research Council (NARC) throughout the Terai region in alpha lattice design with two replications. Data on different yield attributing traits were recorded. In the CVT-TTL 2016/17 highly significant difference (p